Oscillatory Modes оf the Atmosphere оf Jupiter аnd Venus - I. S. Afanasyev; O. Y. Slutskaya; R. G. Zakinyan (Наука. Инновации. Технологии, 2023)
Introduction. The article studies the oscillatory modes of the atmosphere of two planets (Jupiter, Venus), taking into account the influence of axial rotation, which affects the occurrence of beating and resonance, and comparing their parameters with the parameters of the Earth’s atmosphere.Materials and research methods. We consider fluctuations in the atmosphere, which was initially in a state of statics, caused by the initial temperature rise near the earth's surface and the daily rotation of the earth. To describe them, a system is used that includes the equation of motion in the Euler form and expressions that take into account the distribution of temperature and air pressure with height. The case when the rotation of the Earth around its axis leads to significant periodic temperature changes is considered in detail.Research results and their discussion. The values of the main parameters of the atmosphere of Jupiter and Venus are found in order to study the oscillatory regimes of the atmospheres on these planets and build an appropriate mathematical model. At the beginning, we find the standard parameters of velocity amplitudes, temperatures, Brunt-Väisälä frequencies in order to calculate the quantities included in the system of equations describing the fluctuations of air in the atmosphere and build the corresponding graphs of these equations for the purpose of their further analysis. Solutions for oscillatory processes are obtained when daily changes in air temperature are taken into account.Conclusions. It is shown that in the standard atmosphere the axial rotation of the planet does not affect the oscillatory processes in the atmosphere, while the terrain is taken into account. However, there is a case when the difference between the above frequencies is extremely small or zero (this is possible at). If the frequency of Brent – Väisälä coincides with the frequency of the daily rotation of the Earth or their difference is insignificant, then phenomena such as resonance or beats occur, which are considered in detail.